(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Academic integrity and fair student assessment are cornerstones of higher education worldwide. Universities are responsible for both educating students and evaluating their performance transparently, impartially, and ethically. However, the rapid growth of higher education, technological advances, and increasing academic pressure have led to a rise in plagiarism, cheating, biased evaluations, and the misuse of artificial intelligence. These issues raise serious ethical and legal concerns regarding students’ rights, institutional accountability, and the value of academic credentials. This paper examines the ethical and legal aspects of student assessment and academic integrity in universities, with a particular focus on India. It explores the meaning of academic integrity, identifies key ethical challenges in assessment, and analyzes the relevant legal framework, including constitutional safeguards and regulations from bodies like the University Grants Commission. The paper also assesses how courts have handled disputes involving unfair evaluations and academic misconduct, highlights gaps in enforcement, and compares Indian practices to global standards. This paper observed the ethical challenges of student assessments can be drawn a solution to tackle the same with the help of various tackiest. Also researcher will study about the challenges in the implementation of the existing legal framework. Like lack of awareness implementation issues, technological aspect, analysis of misbehavior, infrastructural defects etc. under the University Grant Commission it has been guided to follow certain guidelines for the ethical and rational behavior of the student & teacher. Also the constitution of India carries the important features under Article 14 & 21 equality before the law it provides protection of law and fare treatment to the students. In conclusion, this study recommends reforms to boost ethical awareness, ensure transparent assessments, improve regulatory mechanisms, and address new challenges like AI-driven academic dishonesty. It stresses that a balanced strategy, combining legal enforcement with ethical education, is vital for upholding academic standards and protecting students’ rights